Market-dependent production set - Henrik Egbert; Nadeem Naqvi (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
A country's production possibility frontier or PPF is defined as the boundary of its economy's production set in the net output space for a given technology and fixed quantities of primary factors of production. In general equilibrium theory, exogenous changes in technology or primary-factor supplies alter equilibrium prices; however, government-policy induced domestic relative commodity price changes do not alter the shape of an economy's production set. We show that, under international capital mobility, which is empirically significant, the shape of a country's production set does, in fact, depend on market forces and this shape can be manipulated by government policy.
Keywords: A20; D50; E23; F11; F21; 330; general equilibrium; production possibility frontier; production set; international capital mobility; economic policy; Technische Effizienz; Allgemeines Gleichgewicht; Kapitalmobilität; Wirtschaftspolitik; Theorie